New strategy for diene synthesis : application in total synthesis of Palmerolide A - Wen, Zhenkang (2013)
Palladium-catalyzed alkenylation offers one of the most efficient methods for the synthesis of functionalized butadienes. However, due to the need for pre-functionalization of reactants and undesirable formation of stoichiometric amount of waste in the reactions, these processes were rendered neither atom-economical nor environmentally benign. The emphasis of this thesis is focused on the design and development of a palladium-catalyzed cross-coupling reaction of unactivated alkenes with acrylates for the construction of 1,3-diene motifs and its application towards a total synthesis of the natural product, Palmerolide A. In the first introduction chapter, a summary of established methodologies in the construction of 1,3-butadiene system is outlined, ranging from carbonyl olefination to recently emerging olefin metathesis. In particular, the strategy of transition metal-catalyzed alkenylation is thoroughly and intensively discussed. With the increasing demand for more atom- and step-economical methods, we have developed a direct and efficient palladium-catalyzed method for the cross-coupling of homoallylic and allylic alcohols with acrylates that produces dienic alcohols in moderate to high yields, and with good stereoselectivity.